Separator for non-aqueous secondary battery and non-aqueous secondary battery
By adding barium sulfate particles of specific particle size and proportions and a heat-resistant porous layer of heat-resistant resin to the separator of the non-aqueous secondary battery, the problem of easy cracking and insufficient adhesion at high temperatures is solved, and the safety and production efficiency of the battery are improved.
Patent Information
- Application Number
- JP2020130639
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2020-07-31
- Publication Date
- 2025-02-12
- Estimated Expiration
- 2040-07-31
AI Technical Summary
The separator of the existing non-aqueous secondary battery is prone to rupture or shrinkage at high temperatures, and its adhesion to the electrodes is insufficient, which affects the safety and production efficiency of the battery.
A heat-resistant porous layer containing barium sulfate particles with an average particle size of 0.01 μm to 0.30 μm and a heat-resistant resin was used to combine it on the porous substrate, and the volume ratio of barium sulfate particles was controlled between 5% and 30%, ensuring adhesion and heat resistance between the separator and the substrate.
It improves the heat resistance and peel resistance of the diaphragm, ensures that the battery is not prone to cracking or shrinking at high temperatures, and enhances the safety and production efficiency of the battery.
Smart Images

Figure 0007628780000001
Abstract
Description
[Technical field]
[0001] The present disclosure relates to a separator for a nonaqueous secondary battery and a nonaqueous secondary battery. [Background technology]
[0002] A separator, which is one of the components constituting a nonaqueous secondary battery, is required to have heat resistance so that it does not easily break or shrink even when the inside of the battery becomes hot in order to ensure the safety of the battery. A separator having a porous layer containing a heat-resistant resin and / or inorganic particles on a porous substrate is known as a separator with improved heat resistance. For example, Patent Documents 1 and 2 disclose a separator having a porous layer containing barium sulfate particles on a porous substrate. For example, Patent Documents 3 and 4 disclose a separator having a porous layer containing a resin such as wholly aromatic polyamide and inorganic particles on a porous substrate. For example, Patent Document 5 discloses a separator having a porous layer containing a resin such as wholly aromatic polyamide and barium sulfate particles on a porous substrate. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] Patent No. 5429811 [Patent Document 2] International Publication No. 2014 / 148036 [Patent Document 3] JP 2012-119224 A [Patent Document 4] JP 2019-216033 A [Patent Document 5] Patent No. 6526359 Summary of the Invention [Problem to be solved by the invention]
[0004] In order to ensure the safety of the battery, the separator is required to have an adhesive property that does not easily peel off from the electrode even when it is subjected to an external impact or when the electrode expands and contracts with charging and discharging. In order to ensure the adhesive property of the separator to the electrode, in addition to the adhesive property of the separator surface to the electrode, it is also necessary that each layer constituting the separator does not easily peel off from each other. It is also important from the viewpoint of increasing the manufacturing yield of the battery that each layer constituting the separator does not easily peel off from each other.
[0005] The embodiments of the present disclosure have been made under the above circumstances. An embodiment of the present disclosure has an objective of providing a separator for a non-aqueous secondary battery having a heat-resistant porous layer on a porous substrate, the separator having excellent heat resistance and in which the heat-resistant porous layer is not easily peeled off from the porous substrate. [Means for solving the problem]
[0006] Specific means for solving the above problems include the following aspects.
[0007] <1> A porous substrate; A heat-resistant porous layer provided on one or both sides of the porous substrate and containing a heat-resistant resin and barium sulfate particles; The barium sulfate particles contained in the heat-resistant porous layer have an average primary particle size of 0.01 μm or more and less than 0.30 μm; The volume ratio of the barium sulfate particles to the solid content of the heat-resistant porous layer is 5 volume % or more and less than 30 volume %. Separator for non-aqueous secondary batteries. <2> The volume ratio of the barium sulfate particles to the solid content of the heat-resistant porous layer is 5 volume% or more and less than 27 volume%. <1> The non-aqueous secondary battery separator according to claim 1 . <3> The heat-resistant resin includes at least one selected from the group consisting of wholly aromatic polyamide, polyamideimide, poly-N-vinylacetamide, polyacrylamide, copolymerized polyether polyamide, polyimide, and polyetherimide. <1> or <2> The non-aqueous secondary battery separator according to claim 1 . <4> The peel strength between the porous substrate and the heat-resistant porous layer is 0.30 N / 12 mm or more. <1> ~ <3> 10. The separator for a non-aqueous secondary battery according to claim 9, <5> The nonaqueous secondary battery separator has an area shrinkage rate of 30% or less when heat-treated at 135° C. for 1 hour. <1> ~ <4> 10. The separator for a non-aqueous secondary battery according to claim 9, <6> The nonaqueous secondary battery separator has an area shrinkage rate of 45% or less when heat-treated at 150° C. for 1 hour. <1> ~ <5> 10. The separator for a non-aqueous secondary battery according to claim 9, <7> The heat-resistant porous layer has a porosity of 30% to 70%. <1> ~ <6> 10. The separator for a non-aqueous secondary battery according to claim 9, <8> The mass per unit area of the heat-resistant porous layer is 1.0 g / m on both sides in total. 2 ~30.0g / m 2 That is, <1> ~ <7> 10. The separator for a non-aqueous secondary battery according to claim 9, <9> The nonaqueous secondary battery separator further comprises an adhesive layer as an outermost layer on one or both sides thereof. <1> ~ <8> 10. The separator for a non-aqueous secondary battery according to claim 9, <10> A positive electrode, a negative electrode, and a conductive material disposed between the positive electrode and the negative electrode. <1> ~ <9> and a separator for nonaqueous secondary batteries according to any one of claims 1 to 5, wherein the separator for nonaqueous secondary batteries according to any one of claims 1 to 5 is a separator for nonaqueous secondary batteries. Effect of the Invention
[0008] According to the present disclosure, there is provided a separator for a non-aqueous secondary battery having a heat-resistant porous layer on a porous substrate, the separator having excellent heat resistance and in which the heat-resistant porous layer is not easily peeled off from the porous substrate. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0009] Hereinafter, embodiments of the present disclosure will be described. These descriptions and examples are merely illustrative of the embodiments, and are not intended to limit the scope of the embodiments.
[0010] In the present disclosure, a numerical range indicated using "~" indicates a range that includes the numerical values before and after "~" as the minimum and maximum values, respectively. In the numerical ranges described in the present disclosure in stages, the upper or lower limit value described in one numerical range may be replaced with the upper or lower limit value of another numerical range described in stages. In addition, in the numerical ranges described in the present disclosure, the upper or lower limit value of the numerical range may be replaced with a value shown in the examples.
[0011] In the present disclosure, the term "step" includes not only an independent step, but also a step that cannot be clearly distinguished from other steps, as long as the intended purpose of the step is achieved.
[0012] In the present disclosure, when referring to the amount of each component in a composition, in cases where multiple substances corresponding to each component are present in the composition, unless otherwise specified, it means the total amount of those multiple substances present in the composition.
[0013] In the present disclosure, the particles corresponding to each component may include multiple types. When multiple types of particles corresponding to each component are present in the composition, the particle size of each component means the value for a mixture of the multiple types of particles present in the composition, unless otherwise specified.
[0014] In the present disclosure, MD (Machine Direction) means the longitudinal direction of the porous substrate and separator produced in a longitudinal shape, and TD (Transverse Direction) means the direction perpendicular to MD in the planar direction of the porous substrate and separator. In the present disclosure, TD is also referred to as "width direction".
[0015] In the present disclosure, when the stacking relationship of each layer constituting a separator is expressed as "upper" and "lower", the layer closer to the porous substrate is referred to as "lower" and the layer farther from the porous substrate is referred to as "upper".
[0016] <Separator for non-aqueous secondary batteries> The separator for a nonaqueous secondary battery according to the present disclosure (also referred to as "separator" in the present disclosure) comprises a porous substrate and a heat-resistant porous layer provided on one or both sides of the porous substrate.
[0017] In the separator of the present disclosure, the heat-resistant porous layer contains a heat-resistant resin and barium sulfate particles, the barium sulfate particles contained in the heat-resistant porous layer have an average primary particle size of 0.01 μm or more and less than 0.30 μm, and the volume ratio of the barium sulfate particles to the solid content of the heat-resistant porous layer is 5 vol% or more and less than 30 vol%.
[0018] In the present disclosure, a heat-resistant resin refers to a resin having a melting point of 200° C. or higher, or a resin having no melting point and a decomposition temperature of 200° C. or higher. In other words, a heat-resistant resin in the present disclosure refers to a resin that does not melt or decompose in a temperature range below 200° C.
[0019] The average primary particle size of the barium sulfate particles contained in the heat-resistant porous layer is less than 0.30 μm from the viewpoint of enhancing the heat resistance of the heat-resistant porous layer. When the average primary particle size of the barium sulfate particles is less than 0.30 μm, the heat resistance of the heat-resistant porous layer is enhanced. The mechanism of this is that the surface area (i.e., specific surface area) of the barium sulfate particles per unit volume is increased due to the small particle size of the barium sulfate particles, and therefore the number of contact points between the barium sulfate particles and the heat-resistant resin increases, so that the shrinkage of the heat-resistant porous layer when exposed to high temperatures is suppressed. It is also presumed that the shrinkage of the heat-resistant porous layer when exposed to high temperatures is suppressed due to the fact that many barium sulfate particles with small particle sizes are connected to each other. The average primary particle size of the barium sulfate particles contained in the heat-resistant porous layer is 0.01 μm or more from the viewpoint of suppressing aggregation between the barium sulfate particles and forming a heat-resistant porous layer with high uniformity.
[0020] In the separator of the present disclosure, the volume ratio of barium sulfate particles to the solid content of the heat-resistant porous layer is 5 volume % or more from the viewpoint of obtaining the heat-resistant function of the barium sulfate particles.
[0021] In the separator of the present disclosure, the volume ratio of barium sulfate particles to the solid content of the heat-resistant porous layer is less than 30% by volume from the viewpoint of preventing the heat-resistant porous layer from peeling off from the porous substrate. If the content of barium sulfate particles having a small particle size, that is, an average primary particle size of less than 0.30 μm, is high, the surface of the heat-resistant porous layer becomes flat and the heat-resistant porous layer becomes easily peeled off from the porous substrate. To prevent this phenomenon, the volume ratio of barium sulfate particles to the solid content of the heat-resistant porous layer is less than 30% by volume.
[0022] The functions of the above-mentioned components work synergistically, so that the separator of the present disclosure has excellent heat resistance and the heat-resistant porous layer is not easily peeled off from the porous substrate.
[0023] The porous substrate and the heat-resistant porous layer of the separator of the present disclosure will be described in detail below.
[0024] [Porous base material] In the present disclosure, the porous substrate means a substrate having pores or gaps therein. Examples of such substrates include microporous membranes; porous sheets such as nonwoven fabrics and paper made of fibrous materials; composite porous sheets obtained by laminating one or more other porous layers on these microporous membranes or porous sheets; and the like. In the present disclosure, from the viewpoint of thinning and strength of the separator, microporous membranes are preferred. The microporous membrane means a membrane having a large number of micropores therein, a structure in which the micropores are connected, and which allows gas or liquid to pass from one surface to the other surface.
[0025] The material of the porous substrate is preferably an electrically insulating material, and may be either an organic material or an inorganic material.
[0026] The porous substrate desirably contains a thermoplastic resin to provide the porous substrate with a shutdown function. The shutdown function refers to a function in which, when the battery temperature rises, the constituent material dissolves and blocks the pores of the porous substrate, thereby blocking the movement of ions and preventing thermal runaway of the battery. The thermoplastic resin is preferably a thermoplastic resin having a melting point of less than 200°C. Examples of the thermoplastic resin include polyesters such as polyethylene terephthalate; polyolefins such as polyethylene and polypropylene; and the like, with polyolefins being preferred among them.
[0027] The porous substrate is preferably a microporous membrane containing polyolefin (referred to as a "polyolefin microporous membrane" in the present disclosure). Examples of the polyolefin microporous membrane include polyolefin microporous membranes used in conventional battery separators, and it is desirable to select one having sufficient mechanical properties and ion permeability from these.
[0028] From the viewpoint of exhibiting a shutdown function, the polyolefin microporous membrane is preferably a microporous membrane containing polyethylene, and the polyethylene content is preferably 95% by mass or more based on the total mass of the polyolefin microporous membrane.
[0029] The polyolefin microporous film is preferably a microporous film containing polypropylene, from the viewpoint of heat resistance such that the film does not easily break when exposed to high temperatures.
[0030] From the viewpoint of having a shutdown function and heat resistance that does not easily break when exposed to high temperatures, the polyolefin microporous film is preferably a polyolefin microporous film containing polyethylene and polypropylene. An example of a polyolefin microporous film containing polyethylene and polypropylene is a microporous film in which polyethylene and polypropylene are mixed in one layer. From the viewpoint of achieving both the shutdown function and heat resistance, the microporous film preferably contains 95% by mass or more of polyethylene and 5% by mass or less of polypropylene. Also, from the viewpoint of achieving both the shutdown function and heat resistance, a polyolefin microporous film having a laminated structure of two or more layers, at least one layer containing polyethylene and at least one layer containing polypropylene, is also preferred.
[0031] The polyolefin contained in the polyolefin microporous membrane is preferably a polyolefin having a weight average molecular weight (Mw) of 100,000 to 5,000,000. When the Mw of the polyolefin is 100,000 or more, the microporous membrane can be imparted with sufficient mechanical properties. On the other hand, when the Mw of the polyolefin is 5,000,000 or less, the microporous membrane has good shutdown properties and is easy to mold.
[0032] Examples of methods for producing a polyolefin microporous membrane include a method in which a molten polyolefin resin is extruded through a T-die to form a sheet, which is crystallized, stretched, and then heat-treated to form a microporous membrane; a method in which a molten polyolefin resin together with a plasticizer such as liquid paraffin is extruded through a T-die, cooled to form a sheet, stretched, the plasticizer is extracted, and then heat-treated to form a microporous membrane; and the like.
[0033] Examples of the porous sheet made of a fibrous material include porous sheets such as nonwoven fabrics and papers made of fibrous materials such as polyesters such as polyethylene terephthalate; polyolefins such as polyethylene and polypropylene; heat-resistant resins such as wholly aromatic polyamide, polyamideimide, polyimide, polyethersulfone, polysulfone, polyetherketone, and polyetherimide; and cellulose.
[0034] The composite porous sheet may be a sheet in which a functional layer is laminated on a porous sheet made of a microporous membrane or a fibrous material. Such a composite porous sheet is preferable from the viewpoint of enabling the functional layer to add further functions. From the viewpoint of imparting heat resistance, for example, the functional layer may be a porous layer made of a heat-resistant resin, or a porous layer made of a heat-resistant resin and an inorganic filler. The heat-resistant resin may be one or more heat-resistant resins selected from wholly aromatic polyamide, polyamideimide, polyimide, polyethersulfone, polysulfone, polyetherketone, and polyetherimide. The inorganic filler may be a metal oxide such as alumina; a metal hydroxide such as magnesium hydroxide; or the like. Examples of the composite method include a method of coating a functional layer on a microporous membrane or a porous sheet, a method of bonding a microporous membrane or a porous sheet to a functional layer with an adhesive, and a method of thermocompression bonding a microporous membrane or a porous sheet to a functional layer.
[0035] The surface of the porous substrate may be subjected to various surface treatments in order to improve wettability with the coating liquid for forming the heat-resistant porous layer, as long as the properties of the porous substrate are not impaired. Examples of the surface treatments include corona treatment, plasma treatment, flame treatment, and ultraviolet irradiation treatment.
[0036] [Characteristics of porous substrate] From the viewpoint of increasing the energy density of the battery, the thickness of the porous substrate is preferably 18 μm or less, more preferably 15 μm or less, and even more preferably 12 μm or less, and from the viewpoint of the production yield of the separator and the production yield of the battery, the thickness is preferably 4 μm or more, more preferably 6 μm or more, and even more preferably 8 μm or more.
[0037] The Gurley value (JIS P8117:2009) of the porous substrate is preferably 40 sec / 100 mL to 300 sec / 100 mL, and more preferably 50 sec / 100 mL to 200 sec / 100 mL, from the viewpoint of the balance between ion permeability and suppression of short circuit in the battery.
[0038] The porosity of the porous substrate is preferably 20% to 60% from the viewpoint of obtaining an appropriate membrane resistance and shutdown function. The porosity ε (%) of the porous substrate is calculated by the following formula. ε={1-Ws / (ds·t)}×100 Here, Ws is the basis weight of the porous substrate (g / m 2 ), ds is the true density of the porous substrate (g / cm 3 ), t is the thickness (μm) of the porous substrate. Basis weight is the mass per unit area.
[0039] The average pore size of the porous substrate is preferably 20 nm to 100 nm from the viewpoint of ion permeability or suppression of short circuit in the battery. The average pore size of the porous substrate is measured using a perm porometer (CFP-1500-A manufactured by PMI) in accordance with ASTM E1294-89.
[0040] From the viewpoint of the separator production yield and the battery production yield, the puncture strength of the porous substrate is preferably 150 gf or more, more preferably 200 gf or more. The puncture strength of the porous substrate refers to the maximum puncture strength (gf) measured by a puncture test using a KES-G5 handy compression tester manufactured by Kato Tech Co., Ltd. under the conditions of a needle tip curvature radius of 0.5 mm and a puncture speed of 2 mm / sec.
[0041] [Heat-resistant porous layer] The heat-resistant porous layer has a structure in which a large number of micropores are formed inside and the micropores are interconnected, allowing gas or liquid to pass through from one surface to the other.
[0042] The heat-resistant porous layer may be present on only one side of the porous substrate, or on both sides of the porous substrate. When the heat-resistant porous layer is present on both sides of the porous substrate, the heat resistance of the separator is superior, and the safety of the battery can be improved. In addition, the separator is less likely to curl, and the handling during battery production is excellent. When the heat-resistant porous layer is present on only one side of the porous substrate, the ion permeability of the separator is superior. In addition, the thickness of the entire separator can be reduced, and a battery with a higher energy density can be produced.
[0043] The heat-resistant porous layer contains at least a heat-resistant resin and barium sulfate particles. The heat-resistant porous layer may contain a resin other than the heat-resistant resin. The heat-resistant porous layer may contain inorganic particles other than the barium sulfate particles. The heat-resistant porous layer may contain an organic filler.
[0044] -Heat-resistant resin- The type of heat-resistant resin is not limited as long as it is a resin that does not melt or decompose in a temperature range of less than 200° C. Examples of heat-resistant resins include wholly aromatic polyamide, polyamideimide, poly-N-vinylacetamide, polyacrylamide, copolymerized polyether polyamide, polyimide, and polyetherimide. The heat-resistant resin may be used alone or in combination of two or more kinds.
[0045] Among heat-resistant resins, fully aromatic polyamides are preferred from the viewpoint of durability. Fully aromatic polyamides refer to polyamides whose main chains are composed only of benzene rings and amide bonds. However, a small amount of aliphatic monomers may be copolymerized in fully aromatic polyamides. Fully aromatic polyamides are also called aramids.
[0046] The wholly aromatic polyamide may be meta-type or para-type. Among the wholly aromatic polyamides, meta-type wholly aromatic polyamides are preferred from the viewpoint of easy formation of a porous layer and excellent oxidation-reduction resistance in electrode reactions. Specifically, the wholly aromatic polyamide is preferably polymetaphenylene isophthalamide or polyparaphenylene terephthalamide, and more preferably polymetaphenylene isophthalamide.
[0047] When heat-resistant porous layers are present on both sides of a porous substrate, the type of heat-resistant resin contained in one heat-resistant porous layer may be the same as or different from the type of heat-resistant resin contained in the other heat-resistant porous layer.
[0048] The content of the heat-resistant resin in the heat-resistant porous layer is preferably 85% by mass to 100% by mass, more preferably 90% by mass to 100% by mass, and even more preferably 95% by mass to 100% by mass, based on the total amount of resin in the heat-resistant porous layer.
[0049] -Other resins- The heat-resistant porous layer may contain a resin other than the heat-resistant resin, that is, a resin that melts or decomposes in a temperature range of less than 200° C. Examples of the other resin include polyvinylidene fluoride resins, acrylic resins, fluorine-based rubbers, styrene-butadiene copolymers, homopolymers or copolymers of vinyl nitrile compounds (acrylonitrile, methacrylonitrile, etc.), carboxymethyl cellulose, hydroxyalkyl cellulose, polyvinyl alcohol, polyvinyl butyral, polyvinyl pyrrolidone, polyethers (polyethylene oxide, polypropylene oxide, etc.), polysulfones, polyketones, polyether ketones, polyether sulfones, and mixtures thereof.
[0050] The type and content of the other resin can be selected from the viewpoints of improving the adhesion of the heat-resistant porous layer to the electrodes, the function of binding the barium sulfate particles, the moldability of the heat-resistant porous layer, and the like.
[0051] The content of other resins contained in the heat-resistant porous layer is preferably 0% by mass to 15% by mass, more preferably 0% by mass to 10% by mass, and even more preferably 0% by mass to 5% by mass, based on the total amount of resins contained in the heat-resistant porous layer.
[0052] -Barium sulfate particles- Barium sulfate does not easily decompose the electrolytic solution or electrolyte, and therefore does not easily generate gas. Therefore, by using barium sulfate particles as an inorganic filler in the heat-resistant porous layer, a separator that does not easily generate gas and does not easily cause swelling or deformation of the battery can be obtained.
[0053] The barium sulfate particles may be barium sulfate particles whose surfaces have been modified with a silane coupling agent or the like.
[0054] The particle shape of the barium sulfate particles is not limited, and may be any of spherical, plate-like, needle-like, and irregular shapes. From the viewpoint of suppressing short circuits in a battery or forming a heat-resistant porous layer with high uniformity, the barium sulfate particles are preferably spherical or plate-like particles.
[0055] The average primary particle size of the barium sulfate particles contained in the heat-resistant porous layer is less than 0.30 μm, preferably 0.28 μm or less, and more preferably 0.25 μm or less, from the viewpoint of improving the heat resistance of the heat-resistant porous layer. The average primary particle size of the barium sulfate particles contained in the heat-resistant porous layer is 0.01 μm or more, preferably 0.03 μm or more, and more preferably 0.05 μm or more, from the viewpoint of suppressing aggregation between the barium sulfate particles and forming a heat-resistant porous layer with high uniformity.
[0056] The average primary particle size of barium sulfate particles is determined by measuring the long diameter of 100 randomly selected barium sulfate particles in observation with a scanning electron microscope (SEM) and averaging the long diameters of the 100 particles. The samples used for SEM observation are barium sulfate particles that are the material forming the heat-resistant porous layer, or barium sulfate particles taken out of the heat-resistant porous layer of a separator. There is no limitation on the method for extracting the barium sulfate particles from the heat-resistant porous layer of the separator. For example, the method includes a method of immersing the heat-resistant porous layer peeled off from the separator in an organic solvent that dissolves the resin to extract the barium sulfate particles, and a method of heating the heat-resistant porous layer peeled off from the separator to about 800° C. to remove the resin and extract the barium sulfate particles.
[0057] When heat-resistant porous layers are present on both sides of the porous substrate, the average primary particle size of the barium sulfate particles contained in one heat-resistant porous layer may be the same as or different from the average primary particle size of the barium sulfate particles contained in the other heat-resistant porous layer.
[0058] The volume ratio of the barium sulfate particles in the solid content of the heat-resistant porous layer is 5 volume % or more, preferably 8 volume % or more, and more preferably 10 volume % or more, from the viewpoint of heat resistance of the separator. The volume ratio of the barium sulfate particles in the solid content of the heat-resistant porous layer is less than 30 volume %, preferably less than 27 volume %, and more preferably less than 24 volume %, from the viewpoint of preventing the heat-resistant porous layer from peeling off from the porous substrate.
[0059] The volume ratio Va (vol %) of the barium sulfate particles in the solid content of the heat-resistant porous layer is calculated by the following formula. Va={(Xa / Da) / (Xa / Da+Xb / Db+Xc / Dc+…+Xn / Dn)}×100 Here, among the constituent materials of the heat-resistant porous layer, the barium sulfate particles are a, the other constituent materials are b, c, ..., n, the masses of the constituent materials contained in a predetermined area of the heat-resistant porous layer are Xa, Xb, Xc, ..., Xn (g), and the true densities of the constituent materials are Da, Db, Dc, ..., Dn (g / cm 3 ). Xa, etc. substituted into the above formula are the mass (g) of the constituent material used to form a heat-resistant porous layer of a specified area, or the mass (g) of the constituent material removed from a heat-resistant porous layer of a specified area. The Da and other values substituted in the above formula are the true densities (g / cm) of the constituent materials used to form the heat-resistant porous layer. 3 ), or the true density (g / cm 3 ).
[0060] When heat-resistant porous layers are present on both sides of the porous substrate, the volume ratio of barium sulfate particles in the solid content of one heat-resistant porous layer may be the same as or different from the volume ratio of barium sulfate particles in the solid content of the other heat-resistant porous layer.
[0061] The content of barium sulfate particles in the heat-resistant porous layer is preferably 50% by volume to 100% by volume, more preferably 60% by volume to 100% by volume, and even more preferably 70% by volume to 100% by volume, based on the total amount of inorganic particles in the heat-resistant porous layer.
[0062] -Other inorganic particles- The heat-resistant porous layer may contain inorganic particles other than barium sulfate particles. Examples of the inorganic particles include metal sulfate particles such as strontium sulfate, calcium sulfate, calcium sulfate dihydrate, alumite, and jarosite; metal hydroxide particles such as magnesium hydroxide, aluminum hydroxide, calcium hydroxide, chromium hydroxide, zirconium hydroxide, cerium hydroxide, nickel hydroxide, and boron hydroxide; magnesium oxide, alumina (Al 2 O 3 ), boehmite (alumina monohydrate), titania (TiO 2 ), silica (SiO 2 ), zirconia (ZrO 2 ), barium titanate (BaTiO 3 ), metal oxide particles such as zinc oxide; metal carbonate particles such as calcium carbonate and magnesium carbonate; metal nitride particles such as magnesium nitride, aluminum nitride, calcium nitride, and titanium nitride; metal fluoride particles such as magnesium fluoride and calcium fluoride; clay mineral particles such as calcium silicate, calcium phosphate, apatite, and talc; and the like. As the other inorganic particles, metal hydroxide particles or metal oxide particles are preferred from the viewpoint of stability against the electrolyte and electrochemical stability. The other inorganic particles may be inorganic particles whose surface is modified with a silane coupling agent or the like. The other inorganic particles may be used alone or in combination of two or more.
[0063] When heat-resistant porous layers are present on both sides of a porous substrate, the type of other inorganic particles contained in one heat-resistant porous layer may be the same as or different from the type of other inorganic particles contained in the other heat-resistant porous layer.
[0064] The average primary particle size of the other inorganic particles is preferably 0.01 μm to 5 μm, more preferably 0.05 μm to 3 μm, and even more preferably 0.1 μm to 1 μm. The method for measuring the average primary particle size of the other inorganic particles is the same as the method for measuring the average primary particle size of the barium sulfate particles.
[0065] The particle shape of the other inorganic particles is not limited, and may be any of spherical, plate-like, needle-like, and irregular shapes. The other inorganic particles are preferably spherical or plate-like particles from the viewpoint of suppressing short circuits in the battery or forming a highly uniform heat-resistant porous layer.
[0066] The content of other inorganic particles contained in the heat-resistant porous layer is preferably 0 volume % to 50 volume %, more preferably 0 volume % to 40 volume %, and even more preferably 0 volume % to 30 volume %, based on the total amount of inorganic particles contained in the heat-resistant porous layer.
[0067] When heat-resistant porous layers are present on both sides of a porous substrate, the volume proportion of other inorganic particles in the solid content of one heat-resistant porous layer may be the same as or different from the volume proportion of other inorganic particles in the solid content of the other heat-resistant porous layer.
[0068] The volume ratio of the total inorganic particles to the solid content of the heat-resistant porous layer is preferably less than 50 volume%, more preferably less than 45 volume%, even more preferably less than 40 volume%, and even more preferably less than 35 volume%, from the viewpoint of preventing the heat-resistant porous layer from peeling off from the porous substrate. The volume ratio of the total inorganic particles to the solid content of the heat-resistant porous layer is preferably 5 vol % or more, more preferably 10 vol % or more, and even more preferably 15 vol % or more, from the viewpoint of the heat resistance of the separator.
[0069] Volume ratio of inorganic particles to the solid content of the heat-resistant porous layer Va 0 (Volume %) is calculated according to the following formula. Va 0 = {(Xa 0 / Da 0 ) / (Xa 0 / Da 0 +Xb / Db+Xc / Dc+…+Xn / Dn)}×100 Here, among the constituent materials of the heat-resistant porous layer, inorganic particles are 0 and the other constituent materials are b, c, ..., n, and the mass of each constituent material contained in the heat-resistant porous layer of a given area is Xa 0, Xb, Xc, ..., Xn(g), and the true density of each component is Da 0 , Db, Dc, …, Dn (g / cm 3 ). Substituting Xa into the above formula 0 etc. are the mass (g) of the constituent material used to form a heat-resistant porous layer of a given area, or the mass (g) of the constituent material removed from a heat-resistant porous layer of a given area. Substituting Da into the above formula 0 etc. are the true densities (g / cm 3 ), or the true density (g / cm 3 ).
[0070] -Organic filler- The heat-resistant porous layer may contain an organic filler. Examples of the organic filler include particles made of crosslinked polymers such as crosslinked poly(meth)acrylic acid, crosslinked poly(meth)acrylic acid ester, crosslinked polystyrene, crosslinked polysilicone, crosslinked polydivinylbenzene, styrene-divinylbenzene copolymer crosslinked product, melamine resin, phenol resin, and benzoguanamine-formaldehyde condensate; particles made of heat-resistant polymers such as polysulfone, polyacrylonitrile, aramid, and polyacetal; and the like. These organic fillers may be used alone or in combination of two or more. In the present disclosure, the term "(meth)acrylic" means that it may mean either "acrylic" or "methacrylic".
[0071] -Other ingredients- The heat-resistant porous layer may contain additives such as a dispersant such as a surfactant, a wetting agent, an antifoaming agent, and a pH adjuster. The dispersant is added to the coating liquid for forming the heat-resistant porous layer for the purpose of improving dispersibility, coatability, or storage stability. The wetting agent, antifoaming agent, and pH adjuster are added to the coating liquid for forming the heat-resistant porous layer for the purpose of improving compatibility with the porous substrate, suppressing air entrapment in the coating liquid, or adjusting the pH, for example.
[0072] [Characteristics of heat-resistant porous layer] The thickness of the heat-resistant porous layer is preferably 0.5 μm or more on one side, more preferably 1.0 μm or more on one side, and even more preferably 1.5 μm or more on one side, from the viewpoints of heat resistance or handleability of the separator, and is preferably 8.0 μm or less on one side, more preferably 6.0 μm or less on one side, and even more preferably 4.0 μm or less on one side, from the viewpoints of ion permeability and energy density of the battery.
[0073] When the heat-resistant porous layer is present on both sides of the porous substrate, the thickness of the heat-resistant porous layer, as the total thickness of both sides, is preferably 1.0 μm or more, more preferably 2.0 μm or more, and even more preferably 3.0 μm or more, and is preferably 16.0 μm or less, more preferably 12.0 μm or less, and even more preferably 8.0 μm or less.
[0074] When heat-resistant porous layers are present on both sides of a porous substrate, the smaller the difference (μm) between the thickness of one heat-resistant porous layer and the thickness of the other heat-resistant porous layer, the better, and it is preferable that the difference (μm) be 20% or less of the total thickness (μm) of both sides.
[0075] The mass per unit area of the heat-resistant porous layer is set to 1.0 g / m in total for both sides from the viewpoint of heat resistance or handling of the separator, whether the heat-resistant porous layer is on one side or both sides of the porous substrate. 2 More than 2.0 g / m is preferable. 2 More preferably, 3.0 g / m or more 2 More preferably, the total of both surfaces is 30.0 g / m from the viewpoint of ion permeability and the energy density of the battery. 2 Less than 20.0 g / m is preferred. 2 Less than 10.0 g / m is more preferable. 2 The following is even more preferred:
[0076] When the heat-resistant porous layer is present on both sides of the porous substrate, the difference between the mass per unit area of one heat-resistant porous layer and the mass per unit area of the other heat-resistant porous layer (g / m 2 ) is preferably as small as possible from the viewpoint of suppressing curling of the separator or improving the cycle characteristics of the battery, and the total amount (g / m2 ) is preferably 20% or less.
[0077] The porosity of the heat-resistant porous layer is preferably 30% or more, more preferably 35% or more, and even more preferably 40% or more from the viewpoint of ion permeability, and is preferably 70% or less, more preferably 65% or less, and even more preferably 60% or less from the viewpoint of the mechanical strength and heat resistance of the heat-resistant porous layer. The porosity ε (%) of the heat-resistant porous layer is calculated by the following formula. ε={1-(Wa / da+Wb / db+Wc / dc+…+Wn / dn) / t}×100 Here, the constituent materials of the heat-resistant porous layer are a, b, c, ..., n, and the masses per unit area of each constituent material are Wa, Wb, Wc, ..., Wn (g / cm 2 ), and the true densities of the constituent materials are da, db, dc, …, dn (g / cm 3 ) and the thickness of the heat-resistant porous layer is t (cm).
[0078] The average pore size of the heat-resistant porous layer is preferably 10 nm to 200 nm. When the average pore size is 10 nm or more, when the heat-resistant porous layer is impregnated with an electrolyte, the pores are less likely to be blocked even if the resin contained in the heat-resistant porous layer swells. When the average pore size is 200 nm or less, the uniformity of ion migration in the heat-resistant porous layer is high, and the cycle characteristics and load characteristics of the battery are excellent.
[0079] The average pore size (nm) of the heat-resistant porous layer is calculated by the following formula, assuming that all pores are cylindrical. d=4V / S In the formula, d is the average pore size (diameter) of the heat-resistant porous layer, and V is the average pore size (diameter) of the heat-resistant porous layer per 1 m 2 S is the pore volume per m of the heat-resistant porous layer. 2 It represents the pore surface area per unit area. Heat-resistant porous layer 1m 2 The pore volume V per unit area is calculated from the porosity of the heat-resistant porous layer. Heat-resistant porous layer 1m 2 The surface area S of each pore is calculated by the following method. First, the specific surface area (m 2 / g) and the specific surface area of the separator (m 2 / g) is calculated from the amount of nitrogen gas adsorption by applying the BET equation to the nitrogen gas adsorption method. 2 / g) for each basis weight (g / m 2 ) and multiply each 1m 2 The pore surface area per square meter of the porous substrate is then calculated. 2 The pore surface area per 1 m of separator 2 The surface area of the heat-resistant porous layer is calculated by subtracting the surface area of the pores per m 2 The pore surface area S per unit area is calculated. The basis weight is the mass per unit area.
[0080] From the viewpoint of the adhesive strength of the separator to the electrode, the peel strength between the porous substrate and the heat-resistant porous layer is preferably 0.30 N / 12 mm or more, more preferably 0.40 N / 12 mm or more, and even more preferably 0.50 N / 12 mm or more. From the above viewpoint, the higher the peel strength between the porous substrate and the heat-resistant porous layer, the more preferable, but the peel strength is usually 2.00 N / 12 mm or less. When the separator has a heat-resistant porous layer on both sides of the porous substrate, the peel strength between the porous substrate and the heat-resistant porous layer is preferably within the above range on both sides of the porous substrate.
[0081] The peel strength (N / 12 mm) between the porous substrate and the heat-resistant porous layer is determined by a T-peel test in which the separator is peeled in the MD direction. The test piece is a rectangle with MD 70 mm and TD 12 mm, and the tensile speed of the T-peel test is 300 mm / min.
[0082] [Adhesive layer] The separator of the present disclosure may further have layers other than the porous substrate and the heat-resistant porous layer. Examples of the layers include an adhesive layer. The adhesive layer is provided as the outermost layer of the separator, and is a layer that adheres to the electrode when the separator and the electrode are stacked and pressed or hot-pressed.
[0083] Examples of materials constituting the adhesive layer include resins, inorganic fillers, and organic fillers. Examples of the form of the adhesive layer include a porous layer having many fine pores inside and allowing gas or liquid to pass from one surface to the other surface; a porous coating having many fine pores; and a layer in which many particles are arranged in the surface direction and gas or liquid can pass from one surface to the other surface through the gaps between the particles.
[0084] Examples of the form of the resin constituting the adhesive layer include fibril resin, film-like resin, and particulate resin. The inorganic filler or organic filler may be connected by the resin in these forms and contained in the adhesive layer.
[0085] Examples of resins that may form the adhesive layer include polyvinylidene fluoride resins, acrylic resins, fluorine-based rubbers, styrene-butadiene copolymers, homopolymers or copolymers of vinyl nitrile compounds (acrylonitrile, methacrylonitrile, etc.), carboxymethyl cellulose, hydroxyalkyl cellulose, polyvinyl alcohol, polyvinyl butyral, polyvinylpyrrolidone, polyethers (polyethylene oxide, polypropylene oxide, etc.), polysulfones, polyketones, polyether ketones, polyether sulfones, and mixtures thereof.
[0086] In the case where the adhesive layer contains an inorganic filler, examples of the inorganic filler include metal sulfate particles such as barium sulfate, strontium sulfate, calcium sulfate, calcium sulfate dihydrate, alumite, and jarosite; metal hydroxide particles such as magnesium hydroxide, aluminum hydroxide, calcium hydroxide, chromium hydroxide, zirconium hydroxide, cerium hydroxide, nickel hydroxide, and boron hydroxide; magnesium oxide, alumina (Al 2 O 3 ), boehmite (alumina monohydrate), titania (TiO 2 ), silica (SiO 2 ), zirconia (ZrO 2 ), barium titanate (BaTiO 3), metal oxide particles such as zinc oxide; metal carbonate particles such as calcium carbonate and magnesium carbonate; metal nitride particles such as magnesium nitride, aluminum nitride, calcium nitride, and titanium nitride; metal fluoride particles such as magnesium fluoride and calcium fluoride; clay mineral particles such as calcium silicate, calcium phosphate, apatite, and talc; and the like. These inorganic fillers may be inorganic fillers whose surfaces have been modified with a silane coupling agent or the like. These inorganic fillers may be used alone or in combination of two or more.
[0087] When the adhesive layer contains an organic filler, examples of the organic filler include particles made of crosslinked polymers such as crosslinked poly(meth)acrylic acid, crosslinked poly(meth)acrylic acid ester, crosslinked polystyrene, crosslinked polysilicone, crosslinked polydivinylbenzene, styrene-divinylbenzene copolymer crosslinked product, melamine resin, phenol resin, benzoguanamine-formaldehyde condensate, etc.; particles made of heat-resistant polymers such as polysulfone, polyacrylonitrile, aramid, polyacetal, etc. These organic fillers may be used alone or in combination of two or more.
[0088] Examples of separators having an adhesive layer include a separator having heat-resistant porous layers on both sides of a porous substrate and an adhesive layer on each of the heat-resistant porous layers; a separator having heat-resistant porous layers on both sides of a porous substrate and an adhesive layer on one of the heat-resistant porous layers; a separator having a heat-resistant porous layer on one side of a porous substrate and an adhesive layer on the other side of the porous substrate; a separator having a heat-resistant porous layer on one side of a porous substrate and an adhesive layer on the heat-resistant porous layer; and a separator having a heat-resistant porous layer on one side of a porous substrate and an adhesive layer on the other side of the porous substrate and on the heat-resistant porous layer.
[0089] [Separator characteristics] From the viewpoint of the mechanical strength of the separator, the thickness of the separator is preferably 8 μm or more, more preferably 10 μm or more, and even more preferably 12 μm or more, and from the viewpoint of the energy density of the battery, the thickness is preferably 25 μm or less, more preferably 22 μm or less, and even more preferably 20 μm or less.
[0090] From the viewpoint of the mechanical strength of the separator or the short circuit resistance of the battery, the puncture strength of the separator is preferably 150 gf to 1000 gf, more preferably 200 gf to 600 gf. The method for measuring the puncture strength of the separator is the same as the method for measuring the puncture strength of the porous substrate.
[0091] The porosity of the separator is preferably 30% to 70%, more preferably 35% to 65%, and even more preferably 40% to 60%, from the viewpoints of adhesion to the electrodes, handling properties of the separator, ion permeability, and mechanical strength.
[0092] The Gurley value (JIS P8117:2009) of the separator is preferably 80 sec / 100 mL to 400 sec / 100 mL, and more preferably 120 sec / 100 mL to 300 sec / 100 mL, from the viewpoints of the mechanical strength and ion permeability of the separator.
[0093] The separator preferably has an area shrinkage rate of 30% or less, more preferably 20% or less, and even more preferably 15% or less, when heat-treated at 135° C. for 1 hour.
[0094] The separator preferably has an area shrinkage rate of 45% or less, more preferably 30% or less, and even more preferably 20% or less, when heat-treated at 150° C. for 1 hour.
[0095] The area shrinkage rate when the separator is heat-treated at 135° C. or 150° C. for 1 hour is determined by the following measurement method. The separator is cut into a rectangle with MD 180mm and TD 60mm to be used as a test specimen. Marks are made on this test specimen at points 20mm and 170mm from one end on the line that bisects TD (referred to as points A and B, respectively). In addition, marks are made on the line that bisects MD at points 10mm and 50mm from one end (referred to as points C and D, respectively). A clip is attached to the marked test specimen (the clip is attached between the end closest to point A and point A), and the specimen is hung in an oven with the temperature adjusted to 135℃ or 150℃, and heat-treated for 1 hour in an untensioned state. The lengths between A, B and CD are measured before and after heat treatment, and the area shrinkage is calculated using the following formula. Area shrinkage rate (%) = {1 - (AB length after heat treatment ÷ AB length before heat treatment) × (CD length after heat treatment ÷ CD length before heat treatment)} × 100
[0096] The area shrinkage rate when the separator is heat-treated can be controlled by the volume ratio of barium sulfate particles in the heat-resistant porous layer, the thickness of the heat-resistant porous layer, the porosity of the heat-resistant porous layer, and the like.
[0097] [Separator manufacturing method] The separator of the present disclosure can be manufactured, for example, by forming a heat-resistant porous layer on a porous substrate by a wet coating method or a dry coating method. In the present disclosure, the wet coating method is a method in which a coating layer is solidified in a coagulating liquid, and the dry coating method is a method in which a coating layer is dried and solidified. An embodiment example of the wet coating method will be described below.
[0098] The wet coating method is a method in which a coating liquid containing a heat-resistant resin and barium sulfate particles is applied onto a porous substrate, the substrate is immersed in a coagulating liquid to solidify the coating layer, and the substrate is removed from the coagulating liquid, washed with water, and dried.
[0099] The coating liquid for forming the heat-resistant porous layer is prepared by dissolving or dispersing a heat-resistant resin and barium sulfate particles in a solvent. If necessary, other components than the heat-resistant resin and inorganic particles are dissolved or dispersed in the coating liquid.
[0100] The solvent used in preparing the coating liquid includes a solvent that dissolves the heat-resistant resin (hereinafter, also referred to as a "good solvent.") Examples of the good solvent include polar amide solvents such as N-methylpyrrolidone, dimethylacetamide, and dimethylformamide.
[0101] The solvent used in preparing the coating liquid may contain a phase separation agent that induces phase separation from the viewpoint of forming a porous layer having a good porous structure. Therefore, the solvent used in preparing the coating liquid may be a mixed solvent of a good solvent and a phase separation agent. It is preferable that the phase separation agent is mixed with the good solvent in an amount within a range that ensures a viscosity suitable for coating. Examples of the phase separation agent include water, methanol, ethanol, propyl alcohol, butyl alcohol, butanediol, ethylene glycol, propylene glycol, and tripropylene glycol.
[0102] When the solvent used to prepare the coating liquid is a mixed solvent of a good solvent and a phase separation agent, the mixed solvent preferably contains 60 mass % or more of the good solvent and 5 mass % to 40 mass % of the phase separation agent from the viewpoint of forming a good porous structure.
[0103] The resin concentration in the coating liquid is preferably 1% by mass to 20% by mass in order to form a good porous structure, and the inorganic particle concentration in the coating liquid is preferably 0.5% by mass to 50% by mass in order to form a good porous structure.
[0104] The coating liquid may contain a dispersant such as a surfactant, a wetting agent, an antifoaming agent, a pH adjuster, etc. These additives may remain in the heat-resistant porous layer as long as they are electrochemically stable within the range of use of the nonaqueous secondary battery and do not inhibit the reaction within the battery.
[0105] Examples of a means for applying the coating liquid to the porous substrate include a Mayer bar, a die coater, a reverse roll coater, a roll coater, a gravure coater, etc. When the heat-resistant porous layer is formed on both sides of the porous substrate, it is preferable from the viewpoint of productivity to apply the coating liquid to both sides of the porous substrate simultaneously.
[0106] The coating layer is solidified by immersing the porous substrate on which the coating layer is formed in a coagulation liquid to induce phase separation in the coating layer while solidifying the resin, thereby obtaining a laminate consisting of the porous substrate and the heat-resistant porous layer.
[0107] The solidification liquid generally contains the good solvent and phase separation agent used in preparing the coating liquid, and water. It is preferable from the viewpoint of productivity that the mixing ratio of the good solvent and the phase separation agent is the same as the mixing ratio of the mixed solvent used in preparing the coating liquid. The content of water in the solidification liquid is preferably 40% by mass to 90% by mass from the viewpoints of forming a porous structure and productivity. The temperature of the solidification liquid is, for example, 20°C to 50°C.
[0108] After the coating layer is solidified in the coagulating liquid, the laminate is lifted out of the coagulating liquid and washed with water. The coagulating liquid is removed from the laminate by washing with water. Furthermore, water is removed from the laminate by drying. The washing with water is performed, for example, by conveying the laminate in a water bath. The drying is performed, for example, by conveying the laminate in a high-temperature environment, by blowing air on the laminate, by bringing the laminate into contact with a heat roll, or the like. The drying temperature is preferably 40°C to 80°C.
[0109] The separator of the present disclosure may also be manufactured by a dry coating method, which is a method in which a coating liquid is applied to a porous substrate, and the coating layer is dried to volatilize and remove the solvent, thereby forming a heat-resistant porous layer on the porous substrate.
[0110] The separator of the present disclosure can also be manufactured by a method in which the heat-resistant porous layer is prepared as an independent sheet, the heat-resistant porous layer is laminated on a porous substrate, and the layers are combined by thermocompression bonding or an adhesive. Examples of a method for preparing the heat-resistant porous layer as an independent sheet include a method in which the heat-resistant porous layer is formed on a release sheet by applying the above-mentioned wet coating method or dry coating method.
[0111] When the separator of the present disclosure has an adhesive layer, the adhesive layer can be formed by a wet coating method or a dry coating method. The wet coating method of the adhesive layer is the same as the wet coating method of the heat-resistant porous layer. The dry coating method of the adhesive layer may be the same as the dry coating method of the heat-resistant porous layer, or may be a method of coating and drying an aqueous dispersion containing the constituent materials. The adhesive layer formed on the release sheet may be superimposed on the porous substrate or the heat-resistant porous layer, and may be composited by thermocompression or an adhesive.
[0112] The adhesive layer can be formed after forming a heat-resistant porous layer on the porous substrate. Alternatively, an adhesive layer may be provided on one side of the porous substrate, and then a heat-resistant porous layer may be formed on the other side of the porous substrate. Alternatively, a heat-resistant porous layer and an adhesive layer may be simultaneously formed on the porous substrate by applying a plurality of layers of a plurality of types of coating liquids on the porous substrate.
[0113] <Non-aqueous secondary battery> The nonaqueous secondary battery of the present disclosure is a nonaqueous secondary battery that obtains electromotive force by doping and dedoping lithium ions, and includes a positive electrode, a negative electrode, and the separator for a nonaqueous secondary battery of the present disclosure. Doping means occlusion, support, adsorption, or insertion, and refers to the phenomenon in which lithium ions enter the active material of an electrode such as a positive electrode.
[0114] The nonaqueous secondary battery of the present disclosure has a structure in which, for example, a battery element in which a negative electrode and a positive electrode face each other with a separator interposed therebetween is enclosed in an exterior material together with an electrolyte solution. The nonaqueous secondary battery of the present disclosure is suitable for nonaqueous electrolyte secondary batteries, particularly lithium ion secondary batteries.
[0115] Hereinafter, examples of the positive electrode, negative electrode, electrolyte, and exterior material included in the nonaqueous secondary battery of the present disclosure will be described.
[0116] An example of the positive electrode is a structure in which an active material layer containing a positive electrode active material and a binder resin is formed on a current collector. The active material layer may further contain a conductive additive. Examples of the positive electrode active material include lithium-containing transition metal oxides, specifically LiCoO 2 , LiNiO 2, LiMn 1 / 2 Ni 1 / 2 O 2 , LiCo 1 / 3 Mn 1 / 3 Ni 1 / 3 O 2 , LiMn 2 O 4 , LiFePO 4 , LiCo 1 / 2 Ni 1 / 2 O 2 , LiAl 1 / 4 Ni 3 / 4 O 2 Examples of the binder resin include polyvinylidene fluoride resin, styrene-butadiene copolymer, etc. Examples of the conductive assistant include carbon materials such as acetylene black, ketjen black, graphite powder, etc. Examples of the current collector include aluminum foil, titanium foil, stainless steel foil, etc., having a thickness of 5 μm to 20 μm.
[0117] An example of the negative electrode is a structure in which an active material layer containing a negative electrode active material and a binder resin is formed on a current collector. The active material layer may further contain a conductive assistant. The negative electrode active material may be a material capable of electrochemically absorbing lithium ions, specifically, for example, a carbon material; an alloy of lithium with silicon, tin, aluminum, or the like; Wood's alloy; and the like. The binder resin may be, for example, a polyvinylidene fluoride resin, a styrene-butadiene copolymer, and the like. The conductive assistant may be, for example, a carbon material such as acetylene black, ketjen black, graphite powder, or ultrafine carbon fiber. The current collector may be, for example, a copper foil, a nickel foil, a stainless steel foil, or the like having a thickness of 5 μm to 20 μm. In addition, instead of the above-mentioned negative electrode, a metallic lithium foil may be used as the negative electrode.
[0118] The electrolyte is a solution in which a lithium salt is dissolved in a non-aqueous solvent. Examples of the lithium salt include LiPF 6 , LiBF 4 , LiClO 4Examples of the non-aqueous solvent include cyclic carbonates such as ethylene carbonate, propylene carbonate, fluoroethylene carbonate, difluoroethylene carbonate, and vinylene carbonate; chain carbonates such as dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, and fluorine-substituted derivatives thereof; and cyclic esters such as γ-butyrolactone and γ-valerolactone; which may be used alone or in combination. As the electrolyte, a solution in which a cyclic carbonate and a chain carbonate are mixed in a mass ratio (cyclic carbonate:chain carbonate) of 20:80 to 40:60 and a lithium salt is dissolved in the range of 0.5 mol / L to 1.5 mol / L is suitable.
[0119] Examples of the exterior material include a metal can, an aluminum laminate film pack, etc. The shape of the battery may be rectangular, cylindrical, coin-shaped, etc., and the separator of the present disclosure is suitable for any shape.
[0120] The nonaqueous secondary battery of the present disclosure can be produced by producing a laminate in which the separator of the present disclosure is disposed between a positive electrode and a negative electrode, and then using this laminate by, for example, any of the following methods (1) to (3). Hereinafter, performing a heat press treatment after impregnating the separator with an electrolyte is referred to as "wet heat press", and performing a heat press treatment without impregnating the separator with an electrolyte is referred to as "dry heat press".
[0121] (1) The laminate is heat-pressed (dry heat pressed) to bond the electrodes and separator, then housed in an exterior material (e.g., an aluminum laminate film pack; the same applies below), an electrolyte is injected into it, and the interior of the exterior material is evacuated. After that, the laminate is further heat-pressed (wet heat pressed) on top of the exterior material to bond the electrodes and separator and seal the exterior material.
[0122] (2) The laminate is placed in an exterior packaging material, an electrolyte is injected into it, and a vacuum is created inside the exterior packaging material. The laminate is then heat pressed (wet heat pressed) from above the exterior packaging material to bond the electrodes and separator together and seal the exterior packaging material.
[0123] (3) The laminate is heat pressed (dry heat pressed) to bond the electrodes and separator, then housed in an exterior packaging material, an electrolyte is injected into it, a vacuum is created inside the exterior packaging material, and the exterior packaging material is then sealed.
[0124] The conditions for the wet heat press in the above manufacturing method are preferably a press temperature of 70°C to 110°C and a press pressure of 0.5 MPa to 2 MPa. The conditions for the dry heat press in the above manufacturing method are preferably a press temperature of 20°C to 100°C and a press pressure of 0.5 MPa to 9 MPa. The press time is preferably adjusted according to the press temperature and press pressure, for example, within the range of 0.5 minutes to 60 minutes.
[0125] When manufacturing a laminate in which a separator is disposed between a positive electrode and a negative electrode, the method of disposing the separator between the positive electrode and the negative electrode may be a method of stacking at least one layer of a positive electrode, a separator, and a negative electrode in this order (a so-called stack method), or a method of stacking a positive electrode, a separator, a negative electrode, and a separator in this order and winding them in the length direction. EXAMPLES
[0126] The separator and nonaqueous secondary battery of the present disclosure will be described in more detail below with reference to examples. The materials, amounts, ratios, processing procedures, etc. shown in the following examples can be changed as appropriate without departing from the spirit of the present disclosure. Therefore, the scope of the separator and nonaqueous secondary battery of the present disclosure should not be interpreted as being limited by the specific examples shown below.
[0127] <Measurement and evaluation methods> The measurement and evaluation methods applied in the examples and comparative examples are as follows.
[0128] [Average primary particle size of barium sulfate particles] Barium sulfate particles before being added to a coating liquid for forming a heat-resistant porous layer were used as a sample, and the major axis of 100 randomly selected particles was measured in observation with a scanning electron microscope (SEM), and the average value was calculated to obtain the average primary particle diameter (μm) of the barium sulfate particles. The magnification of the SEM was 50,000 to 300,000 times.
[0129] [Barium sulfate particle content] The volume percentage Va (vol %) of the barium sulfate particles was calculated from the amounts of barium sulfate particles and heat-resistant resin used in the coating liquid for forming the heat-resistant porous layer and the true density according to the following formula. Va={(Xa / Da) / (Xa / Da+Xb / Db)}×100 Here, the barium sulfate particles are a, the heat-resistant resin is b, the amounts of each component material used are Xa and Xb (g), and the true densities of each component material are Da and Db (g / cm 3 ).
[0130] [Thickness of porous substrate and separator] The thickness (μm) of the porous substrate and the separator was measured at 20 points within a 10 cm square using a contact thickness meter (Mitutoyo Corporation, LITEMATIC VL-50S) and the average was calculated. A spherical probe with a sphere radius of 10 mm (Mitutoyo Corporation, carbide spherical probe φ10.5) was used as the measurement terminal, and it was adjusted so that a load of 0.19 N was applied during the measurement.
[0131] [Thickness of heat-resistant porous layer] The thickness of the heat-resistant porous layer (total of both sides, μm) was determined by subtracting the thickness (μm) of the porous substrate from the thickness (μm) of the separator.
[0132] [Mass of heat-resistant porous layer] The separator was cut into a 10cm x 10cm piece, the mass was measured, and the mass was divided by the area to determine the separator basis weight (g / m 2 The porous substrate used in the manufacture of the separator was cut to a size of 10 cm x 10 cm, the mass was measured, and the mass was divided by the area to obtain the basis weight (g / m2) of the porous substrate. 2The mass per unit area of the heat-resistant porous layer (total of both sides, g / m2) was calculated by subtracting the basis weight of the porous substrate from the basis weight of the separator. 2 ) was sought.
[0133] [Porosity of porous substrate] The porosity ε (%) of the porous substrate was calculated by the following formula. ε={1-Ws / (ds·t)}×100 Here, Ws is the basis weight of the porous substrate (g / m 2 ), ds is the true density of the porous substrate (g / cm 3 ), and t is the thickness of the porous substrate (μm).
[0134] [Porosity of heat-resistant porous layer] The porosity ε (%) of the heat resistant porous layer was calculated by the following formula. ε={1-(Wa / da+Wb / db+Wc / dc+…+Wn / dn) / t}×100 Here, the constituent materials of the heat-resistant porous layer are a, b, c, ..., n, and the masses per unit area of each constituent material are Wa, Wb, Wc, ..., Wn (g / cm 2 ), and the true densities of the constituent materials are da, db, dc, …, dn (g / cm 3 ) and the thickness of the heat-resistant porous layer is t (cm).
[0135] [Gurley value] The Gurley values (sec / 100 mL) of the porous substrate and the separator were measured using a Gurley densometer (Toyo Seiki Co., Ltd., G-B2C) in accordance with JIS P8117:2009.
[0136] [Peel strength between porous substrate and heat-resistant porous layer] A T-peel test was performed on the separator. Specifically, an adhesive tape (3M, #550, 12 mm wide) was attached to one surface of the separator (when attaching, the length direction of the adhesive tape was aligned with the MD of the separator), and the separator was cut into a rectangle with MD 70 mm and TD 12 mm together with the adhesive tape. The adhesive tape was peeled off slightly together with the heat-resistant porous layer directly below, and the two separated ends were held by a Tensilon (Orientec, RTC-1210A) to perform a T-peel test. The adhesive tape was used as a support for peeling the heat-resistant porous layer from the porous substrate. The tensile speed of the T-peel test was 300 mm / min, and the load (N / 12 mm) from 10 mm to 40 mm after the start of the measurement was collected at 0.4 mm intervals, and the average value was calculated. Furthermore, the load (N / 12 mm) of 10 test pieces was averaged.
[0137] [Area shrinkage rate due to heat treatment] The separator was cut into a rectangle with MD 180 mm and TD 60 mm to prepare a test piece. Marks were made on this test piece at 20 mm and 170 mm from one end on the line dividing TD in half (referred to as points A and B, respectively). In addition, marks were made on the line dividing MD in half at 10 mm and 50 mm from one end (referred to as points C and D, respectively). A clip was attached to this (the clip was attached between the end closest to point A and point A), and the specimen was hung in an oven with the temperature adjusted to 135°C or 150°C, and heat-treated for 1 hour under no tension. The lengths between AB and CD were measured before and after heat treatment, and the areal shrinkage was calculated using the following formula. The areal shrinkage of 10 specimens was then averaged.
[0138] Area shrinkage rate (%) = {1 - (AB length after heat treatment ÷ AB length before heat treatment) × (CD length after heat treatment ÷ CD length before heat treatment)} × 100
[0139] <Preparation of separator> [Example 1] As materials for the heat-resistant porous layer, meta-type wholly aromatic polyamide and barium sulfate particles were prepared. The physical properties of these are shown in Table 1.
[0140] A meta-type wholly aromatic polyamide was dissolved in dimethylacetamide (DMAc) so that the resin concentration was 6.5% by mass, and barium sulfate particles were further mixed and stirred to obtain a coating solution (1).
[0141] An appropriate amount of coating liquid (1) was placed on a Mayer bar, and coating liquid (1) was applied to both sides of a polyethylene microporous membrane (thickness 10 μm, porosity 48%, Gurley value 72 sec / 100 mL). At this time, coating was performed so that the coating amount on the front and back of the polyethylene microporous membrane was equal. This was immersed in a coagulation liquid (DMAc:water=50:50 [mass ratio], liquid temperature 40° C.) to solidify the coating layer, and then washed in a water washing tank with water temperature of 40° C. and dried. In this way, a separator in which a heat-resistant porous layer was formed on both sides of the polyethylene microporous membrane was obtained.
[0142] [Examples 2 to 8, Comparative Examples 1 to 4] Each separator was produced in the same manner as in Example 1, except that the particle size and / or the volume ratio of the barium sulfate particles contained in the heat-resistant porous layer was changed to the specifications shown in Table 1.
[0143] Table 1 shows the composition, physical properties and evaluation results of each of the separators of Examples 1 to 8 and Comparative Examples 1 to 4. The meta-type wholly aromatic polyamide used to form the heat-resistant porous layer is shown in Table 1 as "aramid".
[0144] [Table 1]
[0145] [Example 9] An adhesive layer was provided on both sides of the separator of Example 1 by the following method to prepare a separator of Example 9.
[0146] An aqueous dispersion (solid content concentration 7% by mass) was prepared by dispersing polyvinylidene fluoride resin particles (melting point 140°C, volume average particle diameter 0.2 μm) and acrylic resin particles (glass transition temperature 59°C, volume average particle diameter 0.5 μm) in water at a mass ratio of 70:30. The separator of Example 1 was passed between a pair of bar coaters on which an appropriate amount of this aqueous dispersion was placed, and the aqueous dispersion was applied in equal amounts to both sides of the separator, which was then dried. In this way, a separator was obtained in which a heat-resistant porous layer and an adhesive layer were formed on both sides of a polyethylene microporous membrane.
[0147] The adhesive strength to the electrodes was measured for the separator of Example 1 and the separator of Example 9. The separator of Example 9 had a higher adhesive strength to the electrodes than the separator of Example 1. The electrodes and the measurement method used to measure the adhesive strength to the electrodes are as follows.
[0148] - Preparation of positive electrode - 94 parts by mass of lithium cobalt oxide powder, 3 parts by mass of acetylene black, 3 parts by mass of polyvinylidene fluoride resin, and an appropriate amount of N-methyl-2-pyrrolidone were mixed in a twin-arm mixer to prepare a slurry with a polyvinylidene fluoride resin concentration of 5% by mass. This slurry was applied to one side of an aluminum foil with a thickness of 20 μm, dried, and pressed to obtain a positive electrode.
[0149] - Preparation of negative electrode - 300 parts by mass of artificial graphite, 7.5 parts by mass of an aqueous dispersion containing 40% by mass of a modified styrene-butadiene copolymer, 3 parts by mass of carboxymethyl cellulose, and an appropriate amount of water were kneaded in a twin-arm mixer to prepare a slurry. This slurry was applied to one side of a copper foil with a thickness of 10 μm, dried, and pressed to obtain a negative electrode.
[0150] The positive electrode and the negative electrode were cut into a rectangle of 70 mm by 15 mm, and the separator was cut into a rectangle of MD 72 mm by TD 18 mm. The positive electrode, separator, and negative electrode were stacked in this order, and the electrodes and the separator were bonded by heat pressing (85°C, 1 MPa, 30 seconds) to obtain a test piece.
[0151] The test piece was fixed to the lower chuck of a Tensilon (A&D, STB-1225S). At this time, the test piece was fixed to the Tensilon so that the length direction of the test piece (i.e., the MD of the separator) was the direction of gravity. The positive electrode was peeled off from the separator by about 2 cm from the bottom end, and the end was fixed to the upper chuck, and a 180° peel test was performed. The tensile speed of the 180° peel test was 300 mm / min, and the load (N) from 10 mm to 40 mm after the start of the measurement was collected at 0.4 mm intervals, and the average was calculated. The loads of the three test pieces were then averaged to obtain the adhesive strength (N / 15 mm) between the electrode and the separator.
Claims
1. A porous substrate; A heat-resistant porous layer provided on one or both sides of the porous substrate and containing a heat-resistant resin and barium sulfate particles; the heat-resistant resin is at least one selected from the group consisting of wholly aromatic polyamide, polyamideimide, poly-N-vinylacetamide, polyacrylamide, copolymerized polyether polyamide, polyimide, and polyetherimide; the content of the heat-resistant resin in the heat-resistant porous layer is 85% by mass to 100% by mass based on the total amount of the resin in the heat-resistant porous layer; The barium sulfate particles contained in the heat-resistant porous layer have an average primary particle size of 0.01 μm or more and less than 0.30 μm, The volume ratio of the barium sulfate particles to the solid content of the heat-resistant porous layer is 5 volume % or more and less than 30 volume %, The heat-resistant porous layer has a porosity of 30% to 70%. Separator for non-aqueous secondary batteries.
2. 2. The separator for a nonaqueous secondary battery according to claim 1, wherein a volume ratio of the barium sulfate particles to a solid content of the heat-resistant porous layer is 10 volume % or more and less than 30 volume %.
3. 3. The separator for a non-aqueous secondary battery according to claim 1, wherein a peel strength between the porous substrate and the heat-resistant porous layer is 0.30 N / 12 mm or more.
4. 4. The separator for a non-aqueous secondary battery according to claim 1, wherein the separator for a non-aqueous secondary battery has an area shrinkage rate of 30% or less when heat-treated at 135° C. for 1 hour.
5. 5. The separator for a non-aqueous secondary battery according to claim 1, wherein the separator for a non-aqueous secondary battery has an area shrinkage rate of 45% or less when heat-treated at 150° C. for 1 hour.
6. The mass per unit area of the heat-resistant porous layer is 1.0 g / m on both sides in total. 2 ~30.0g / m 2 The separator for a non-aqueous secondary battery according to any one of claims 1 to 5,
7. 7. The non-aqueous secondary battery separator according to claim 1, further comprising an adhesive layer as an outermost layer on one or both sides of the non-aqueous secondary battery separator.
8. A nonaqueous secondary battery comprising: a positive electrode; a negative electrode; and the separator for a nonaqueous secondary battery according to any one of claims 1 to 7, which is disposed between the positive electrode and the negative electrode, and which obtains an electromotive force by doping and dedoping lithium ions.
Citation Information
Patent Citations
Hard alloy
JP1979029811A
Laminated porous film, separator for battery, and battery
JP2011110704A
Separator for nonaqueous secondary battery
JP2011210435A
Separator for nonaqueous electrolyte battery, and nonaqueous electrolyte battery
JP2012119224A
Separator for lithium secondary battery and lithium secondary battery including the same
JP2017191775A